Sensitivity and Specificity of Lateral Flow Antigen Test Kits for COVID-19 in Asymptomatic Population of Quarantine Centre of Province 3 - Shrestha, B.; Neupane, A.K.; Pant, S.; Shrestha, A.; Bastola, A.; Rajbhandari, B.; Thapa, A.; Singh, A. (Kathmandu University Medical Journal, 2020)
Background Nearly after 6 months of the spread of Corona Virus Disease 19, along with the world Nepal is still trying to control the spread and prevent general population from acquiring it. With limited resources in manpower, technology and evidence it has been a difficult battle. But with time and more understanding of the virus new technology to detect the virus are coming up. It is a major breakthrough in the diagnostic field as this helps us in not only detecting the virus but also helps us to mobilize our human resources. This comes in a time where the cases are increasing at an alarming rate. Although numbers of Polymerase Chain Reaction testing have increased but due to the time consuming and the cost wise, we need a faster and equally reliable alternative. Antigen test approved by different countries can be used for point of care, screening and surveillance depending upon the requirements after calculating its sensitivity, specificity and accuracy. Objective To find out sensitivity and specificity of the Antigen test kit for COVID-19. Method Antigen tests were compared with Reverse Transcription Polymerase Chain Reaction as a reference standard in calculated sample size of 113 subjects in a high risk population. Both Reverse Transcription Polymerase Chain Reaction and antigen test were performed in a same subject with in maximum of 2 days’ interval. Convenience sampling technique was used to select the subjects. Ethical approval was taken from Nepal Health Research Council before data collection. Study was done from August to September 2020 from Quarantine center of Province 3. Result There were total of 113 test carried out, among those 47 were positive and 66 were negative in Reverse Transcription Polymerase Chain Reaction. After preparing two by two table, Sensitivity and specificity of the tested was calculated which came out to be 85% and 100% respectively, with accuracy of 93.80%. Conclusion Even though the sensitivity and specificity came to be higher, this test should be interpreted cautiously depending upon the prevalence of Corona Virus Disease 19 in that particular community and the clinical and epidemiological context of the person who has been tested. When in doubt by clinical correlation should be confirmed with Reverse Transcription Polymerase Chain Reaction.